CALCULATING VARIABLE ANNUITY LIABILITY "GREEKS" USING MONTE CARLO SIMULATION. Issue 2 (5th January 2015) - Cathcart, Mark J.; Lok, Hsiao Yen; McNeil, Alexander J.; Morrison, Steven
Abstract: The implementation of hedging strategies for variable annuity products requires the calculation of market risk sensitivities (or "Greeks"). The complex, path-dependent nature of these products means that these sensitivities are typically estimated by Monte Carlo methods. Standard market practice is to use a "bump and revalue" method in which sensitivities are approximated by finite differences. As well as requiring multiple valuations of the product, this approach is often unreliable for higher-order Greeks, such as gamma, and alternative pathwise (PW) and likelihood-ratio estimators should be preferred. This paper considers a stylized guaranteed minimum withdrawal benefit product in which the reference equity index follows a Heston stochastic volatility model in a stochastic interest rate environment. The complete set of first-order sensitivities with respect to index value, volatility and interest rate and the most important second-order sensitivities are calculated using PW, likelihood-ratio and mixed methods. It is observed that the PW method delivers the best estimates of first-order sensitivities while mixed estimation methods deliver considerably more accurate estimates of second-order sensitivities; moreover there are significant computational gains involved in using PW and mixed estimators rather than simple BnR estimators when many Greeks have to be calculated.